2008
DOI: 10.1002/pat.1022
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties and combustion behaviors of UV‐cured phosphate triacrylate/star poly(urethane acrylate) oligomer blends

Abstract: A series of UV-curable intumescent flame retardant resins was obtained by blending phosphate triacrylate (TAEP) in certain ratios with star poly(urethane acrylate) (SPUA) oligomer. The flammability of the cured films was characterized by limited oxygen index (LOI), UL 94, and the cone calorimeter. The results showed that the cured TAEP/SPUA samples greatly expanded while burning. A distinct synergistic effect was found between TAEP and SPUA. TAEP2 sample showed the highest LOI value (41) among all resins. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Their high loadings of flame retardants often inhibit the curing process and result in severe degradation of curable resins, which deteriorates the mechanical and physical properties of the resins. , The additive-type flame retardants can also leach from the matrix by normal service and aging, causing an environmental threat and weakening the flame-retardant effect. By contrast, the reactive-type flame retardants are incorporated into the EA matrix via a chemical copolymerization method. A relatively low content of reactive-type retardants can reduce the flammability of EA significantly and careful selection of the flame retardants can limit detrimental changes to the mechanical and physical properties of the resins to an acceptable level. On the basis of the analysis mentioned above, exploiting novel reactive P–N-containing flame retardants is a promising avenue of research in the flame retardancy of EA resins.…”
Section: Introductionmentioning
confidence: 99%
“…Their high loadings of flame retardants often inhibit the curing process and result in severe degradation of curable resins, which deteriorates the mechanical and physical properties of the resins. , The additive-type flame retardants can also leach from the matrix by normal service and aging, causing an environmental threat and weakening the flame-retardant effect. By contrast, the reactive-type flame retardants are incorporated into the EA matrix via a chemical copolymerization method. A relatively low content of reactive-type retardants can reduce the flammability of EA significantly and careful selection of the flame retardants can limit detrimental changes to the mechanical and physical properties of the resins to an acceptable level. On the basis of the analysis mentioned above, exploiting novel reactive P–N-containing flame retardants is a promising avenue of research in the flame retardancy of EA resins.…”
Section: Introductionmentioning
confidence: 99%
“…So, as compared to additive-type flame retardants, reactive-type flame retardants are more promising and are becoming a trend. 1,2,[5][6][7][8][9] Among the reactive-type flame retardants, monomers or oligomers containing phosphorus used as flame retardants for epoxy acrylate have drawn much attention. In our previous work, we have synthesized a series of novel flame retardants containing phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the same authors blended this six-armed star-shaped urethane acrylate with TAEP. 28 In both studies the highest LOI value was found to be 41. In contrast to the previous study they further investigated the flame retardancy of this new photocurable coating material by UL94 test.…”
Section: Phosphorus-containing Flame-retardant Photocurable Coatingsmentioning
confidence: 93%